2013
DOI: 10.1177/0022034513507065
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Basis of Oral Malodor Development in Humans

Abstract: To better understand the microbial basis of oral malodor development in humans, we used a cross-sectional and longitudinal study design and the pyrosequencing approach to track and compare the tongue microbiota associated with oral malodor in 29 Chinese adults who underwent a consecutive three-day evaluation for the amount of H 2 S excreted orally. Three levels of the oral malodor state (healthy, oral malodor, and severe oral malodor) were defined based on the H 2 S level. Community structure of the tongue pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
65
1
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(79 citation statements)
references
References 27 publications
12
65
1
1
Order By: Relevance
“…Since previous reviews [2,3], Leptotrichia species have been reported in >124 cases [4,7,16,1869,8793], whereby 30 cases involved L. buccalis [4,8,15,21,34,52,56,70–79,87], 24 cases L. wadei [4,20,24,34,37,42,48,56,67,80,81,90,93], 16 cases L. trevisanii [4,5,9,10,13,14,17,37,87], 14 cases L. hofstadii [34,40,49,56,8184,93], 10 cases L. goodfellowii [4,11,12,21,56,74,85,87], eight cases L. hongkongensis [4,6,18,45,47,56], and five L. shahii [34,56,86]. L. trevisanii and L. wadei bacteremia are extremely rare; clinicians should consider these species in cases involving immunocompromised patients with oral lesions [4,5,13,17,87].…”
Section: Figurementioning
confidence: 99%
See 4 more Smart Citations
“…Since previous reviews [2,3], Leptotrichia species have been reported in >124 cases [4,7,16,1869,8793], whereby 30 cases involved L. buccalis [4,8,15,21,34,52,56,70–79,87], 24 cases L. wadei [4,20,24,34,37,42,48,56,67,80,81,90,93], 16 cases L. trevisanii [4,5,9,10,13,14,17,37,87], 14 cases L. hofstadii [34,40,49,56,8184,93], 10 cases L. goodfellowii [4,11,12,21,56,74,85,87], eight cases L. hongkongensis [4,6,18,45,47,56], and five L. shahii [34,56,86]. L. trevisanii and L. wadei bacteremia are extremely rare; clinicians should consider these species in cases involving immunocompromised patients with oral lesions [4,5,13,17,87].…”
Section: Figurementioning
confidence: 99%
“…Saliva, plaque, and the oral mucosal surface of caries patients [34,37,56,67] and the oral cavity and biofilms from oral epithelial cells of a patient with new-onset rheumatoid arthritis [20,48] all contained L. wadei . Patient material from tongue plaque, saliva, and the tongue coating of malodor and halitosis patients [42,81] was isolated with L. wadei present. This bacterium was even isolated from the antral gastric biopsy of a dyspeptic patient [80], smokers’ plaque [90], and oropharyngeal samples (Table 2) [93].…”
Section: Brief Additional Clinical Information On Leptotrichia Speciesmentioning
confidence: 99%
See 3 more Smart Citations